The use of controlled cracking to improve the efficiency of waterjet cutting - Орел, Вадим Николаевич; Щетинин, Виктор Терентиевич; Саленко, Александр Федорович; Яцина, Николай Николаевич (Eastern-European Journal of Enterprise Technologies, 2016)
The study focuses on the possibilities of increasing the production efficiency of waterjet cutting with the aid of mechatronic systems. We have proved the effect of different types of loads and the form of the cut on the cracks in sheet workpieces. A computer simulation of a workpiece load facilitated identifying stress zones along the cutting contours. It is proved that controlling a non-stationary stress state allows limiting the crack growth rate. Increased energy efficiency and performance parameters in a complex-contour cutting of workpieces with an abrasive fluid jet is an important task for operating hydroabrasive technological complexes manufactured in a wide range by foreign and domestic firms. It is found that the most effective cutting is that with pre-loading of sheet blanks with a tensile strength up to 90 MPa. If the sheet thickness exceeds 5-6 mm the effect decreases, whereas materials thicker than 15 mm are processed with additional energy consumption. Thus, it can be assumed that when preloading devices control the stress-strain state (SSS) of the cutting area in quasi-elastic sheet workpieces the processing performance increases and the quality of the cut improves.